THE MODELS OF THE KNOWLEDGE BASE EXPERT SYSTEM FOR APPLICANTS CHOOSING A SPECIALTY IN HIGH SCHOOLS - Kuchakovska, Halyna A. (Educological discourse, 2014)
The main problem in the development of information society in Ukraine is the low competitiveness of youth. This problem occurs because an applicant at the entrance stage cannot say exactly what he/or she wants to do in the future, and vocational guidance centers are unable to provide sufficient information on the profession market and professional requirements. The development of the expert system of professional orientation was suggested in order to improve the performance of such centers. In this paper we suggested an approach to the creation of the knowledge base for the fuzzy logic based expert system of professional orientation in choosing a speciality; analysed three ways of its modelling, made KPI (key performance indicator) characteristic and chose the best one. Further research will be made to create a knowledge base for a particular model.